Identification of two new cytochrome P450 genes and RNA interference to evaluate their roles in detoxification of commonly used insecticides in Locusta migratoria manilensis - Guo, Yanqiong; Zhang, Jianzhen; Yu, Rongrong; Zhu, Kun Yan; Guo, Yaping; Ma, Enbo (My University, 2012)
Cytochrome P450 monooxygenases (cytochrome P450s), found in virtually all living organisms, play an important role in the metabolism of xenobiotics such as drugs, pesticides, and plant toxins. We have previously evaluated the responses of the oriental migratory locust (Locusta migratoria) to the pyrethroid insecticide deltamethrin and revealed that increased cytochrome P450 enzyme activity was due to increased transcription of multiple cytochrome P450 genes. In this study, we identified for the first time two new cytochrome P450 genes, which belong to two novel cytochrome P450 gene families. CYP409A1 belongs to CYP409 family whereas CYP408B1 belongs to CYP408 family. Our molecular analysis indicated that CYP409A1 was mainly expressed in fatbodies, midgut, gastric caecum, foregut and Malpighian tubules of the third- and fourth-instar nymphs, whereas CYP408B1 was mainly expressed in foregut, hindgut and muscle of the insects at all developmental stages examined. The expression of these two cytochrome P450 genes were differentially affected by three representative insecticides, including carbaryl (carbamate), malathion (organophosphate) and deltamethrin (pyrethroid). The exposure of the locust to carbaryl, malathion and deltamethrin resulted in reduced, moderately increased and significantly increased transcript levels, respectively, of the two cytochrome P450 genes. Our further analysis of their detoxification roles by using RNA interference followed by deltamethrin bioassay showed increased nymph mortalities by 21.1% and 16.7%, respectively, after CYP409A1 and CYP408B1 were silenced. These results strongly support our notion that thesthese two new cytochrome P450 genes play an important role in deltamethrin detoxification in the locust.
Citation: Guo, Y., Zhang, J., Yu, R., Zhu, K. Y., Guo, Y., & Ma, E. (2012). Identification of two new cytochrome P450 genes and RNA interference to evaluate their roles in detoxification of commonly used insecticides in Locusta migratoria manilensis. Retrieved from http://krex.ksu.edu
Keywords: Cytochrome P450; Locusta migratoria; Gene expression; Insecticides; RNA interference